Lebensbedingungen im demographischen Wandel: Konsequenzen von Alterung und Schrumpfung für Bildungschancen und medizinische Versorgung in ländlichen Räumen - Schmitz-Veltin, Ansgar (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
For decades the regional development of the Federal Republic of Germany based on the goal of equality of living conditions. Today the adjustment of living conditions in urban and rural areas is mainly fulfilled. Nevertheless, the demographic change, the ageing and shrinking of the population, results in a dismantling of infrastructures in weak populated regions and leads so to a new disadvantage of rural residences. At the example of educational infrastructure and medical care in rural regions the possible consequences of this development are examined.